Rendimiento pronóstico del índice neutrófilos/linfocitos y el índice plaquetas/linfocitos para mortalidad en pacientes con ictus agudo atendidos en un hospital de Loreto 2019-2024 - Vásquez Inga, Sebastian (2025)
Introduction: Acute stroke is one of the leading causes of morbidity and mortality worldwide. The search for hematological indicators that reflect the systemic inflammatory response has allowed us to explore the prognostic value of the neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) in various clinical conditions. In this context, their usefulness as predictors of mortality in patients with acute stroke still needs to be evaluated in local hospital settings. Objective: To evaluate the prognostic performance of the neutrophil/lymphocyte ratio and the platelet/lymphocyte ratio in predicting mortality in patients with acute stroke treated at a hospital in Loreto during the period 2019–2024. Method: Observational, cross sectional, retrospective, and analytical study with a case-control design. Population: The population consisted of 210 patients hospitalized for acute stroke, with a sample of 105 clinical records selected according to inclusion and exclusion criteria. Results: Of the 105 patients with acute stroke analyzed, 60% had elevated INL values ≥ 4 and 64.8% had IPL values ≥ 150. Overall mortality was 33.3%, predominantly in cases of hemorrhagic stroke (50%) compared to ischemic stroke (23.1%), with a significant association (p = 0.004; OR = 3.33; 95% CI: 1.43–7.76). The level of consciousness on admission showed a strong relationship with mortality (p < 0.001), reaching 84.6% of deaths in patients in serious condition (OR = 29.15; 95% CI: 5.59–151.98). Elevated INL (≥ 4) was significantly associated with fatal outcome (47.6% mortality; p < 0.01; OR = 6.73; 95% CI: 2.33–19.35), while IPL ≥ 150 did not reach statistical significance (p = 0.058). In the survival analysis, patients with INL < 4 showed a better prognosis (Log Rank = 10.644; p = 0.00002), while the differences according to IPL were not significant (Log Rank = 2.652; p = 0.103). In addition, hemorrhagic stroke had lower cumulative survival compared to ischemic stroke (Log Rank = 6.788; p = 0.009). Conclusions: INL showed a clear association with mortality in patients with acute stroke, demonstrating better prognostic performance than IPL. Mortality was more frequent in cases of hemorrhagic stroke and in patients with severe levels of consciousness upon admission.